Survey on Nano Technology - Adel Alfoudery; Abdulrahman Alkandari; Samer Moein (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
Recently, Nanotechnology has become a reality of great concerns all over the world, which seeks constitutes serious about expanding the scope of applications and investments of this technique. In this paper, we have introduced nanotechnology, since it has become the first rank among the priorities of scientific research in the world, where the expanded universities, research centers and institutions seek to employ nanotechnology in new products, industries, and technology.  We have discussed types of Nanomaterials in details and focused on the applications that use Nanotechnology. This paper confirms the view of scientists who look at this technique working as a component of the world's future, and a crucial factor that has led and will continue leading the world to a new industrial revolution